2018
DOI: 10.1021/acs.joc.8b02244
|View full text |Cite
|
Sign up to set email alerts
|

Regio- and Diastereoselective Synthesis of Dihydropyrans and Pyranopyrans via Oxonium–Ene Reaction of β-Allenols and Aldehydes

Abstract: Bismuth trifluoromethanesulfonate can be efficiently used for the preparation of dihydropyrans from βallenols and aldehydes by oxonium−ene reaction in good yields. The reaction is highly regioselective. On the other hand, the same reaction with trimethylsilyl trifluoromethanesulfonate at −45 °C affords the hexahydropyrano[4,3-b]pyran skeleton in moderate yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Thus, when β-allenols 112 were reacted with aldehydes 27 in the presence of Bi(OTf) 3 dihydropyrans 113 and 114 were obtained in moderate to good yields (Scheme 62 ). 64 Both aromatic and aliphatic aldehydes worked well under the reaction conditions. However, aromatic aldehydes with electron-donating or electron-withdrawing groups on the aromatic ring gave better yields compared to aliphatic aldehydes.…”
Section: Oxonium-ene Cyclization Reactionsmentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, when β-allenols 112 were reacted with aldehydes 27 in the presence of Bi(OTf) 3 dihydropyrans 113 and 114 were obtained in moderate to good yields (Scheme 62 ). 64 Both aromatic and aliphatic aldehydes worked well under the reaction conditions. However, aromatic aldehydes with electron-donating or electron-withdrawing groups on the aromatic ring gave better yields compared to aliphatic aldehydes.…”
Section: Oxonium-ene Cyclization Reactionsmentioning
confidence: 95%
“…On the other hand, opposite isomer 64'-65' having benzoyl group endo to the pyrroloisoindolone and pyridoisoindolone ring system would be unstable due to the repulsion between benzoyl group and isoindolinone moiety. Another possibility of formation of most stable isomers 64-65 by equilibration of the initially formed compounds 64- 65 38). Further, to confirm that the product was from thermodynamically controlled reaction, compound 64a was treated with KOH in dry MeOH and it was found that the ratio of diastereomers 64a and 64a' was 77:23 (Scheme 39, eq.…”
Section: Scheme 36mentioning
confidence: 99%
“…β-Allenols 409 react with aromatic aldehydes in the presence of Bi(OTf) 3 as Lewis acid catalyst to yield the dihydropyran skeleton 410 in moderate yields ( Scheme 70 , reaction a). 277 When allenols 409 were treated with In(OTf) 3 as Lewis acid catalyst, major efficiency in terms of catalyst loading toward the cocyclization adducts 410 was found ( Scheme 70 , reaction b). 278 Interestingly, reaction of 5,5-dimethyl substituted β-allenol 409a and aldehydes under In(OTf) 3 catalysis exhibited a special behavior.…”
Section: Synthetic Utilitymentioning
confidence: 99%
“…Co-cyclization of allenols with aldehydes through Prins-type processes have also been reported, providing the synthesis of oxacycles with different ring sizes. β-Allenols 409 react with aromatic aldehydes in the presence of Bi­(OTf) 3 as Lewis acid catalyst to yield the dihydropyran skeleton 410 in moderate yields (Scheme , reaction a) . When allenols 409 were treated with In­(OTf) 3 as Lewis acid catalyst, major efficiency in terms of catalyst loading toward the cocyclization adducts 410 was found (Scheme , reaction b) .…”
Section: Synthetic Utilitymentioning
confidence: 99%